Health Examination of The Digestion of Proboscis Monkey (Nasalis larvatus) through Bacteriological Tests on Feces - Maisya, Camalia; Nurliani, Anni; Rezeki, Amalia; Rusmiati, R (Universitas Muhammadiyah Surakarta, 2023)
This study aims to identify bacteria and the prevalence value of bacteria found in probosci's monkey feces as a picture of proboscis monkey digestive health. Seventeen fecal samples from each proboscis monkey, namely Mimin, Chikita, and Pedro, were taken at the Bekantan Rescue Center, Sahabat Bekantan Indonesia Foundation (SBI). Feces were identified by making macroscopic and microscopic observations. Visible observations include consistency, color, mucus, and blood in the physical feces. Microscopic observations were made by culturing feces on Mac Conkey, blood agar, EMBA, DHL agar, and NA media, followed by gram staining and biochemical tests consisting of VP (Voges-Proskaeur) test, methyl red test, indole test, citrate test, and lactose test. The results of identifying 17 feces samples from each probosci's monkey found the presence of E.coli bacteria from microscopic testing. The prevalence of E.coli bacteria in Mimin, Chikita, and Pedro is 41.17%; 35.29%; 35.29%, so it is concluded that the presence of E.coli is a typical bacterium that is not harmful to the digestion of proboscis monkeys, supported by observations on the physical macroscopic feces of good probosci's monkeys.